Does compliance strategy increase compliance? Evidence from Malaysia - Norul Syuhada Abu Hassan,; Mohd Rizal Palil,; Rosiati Ramli,; Ruhanita Maelah, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Due to the significance of tax revenue as the primary source of a country’s income, any leakage due to non-compliance behaviour may impact the country, which will eventually affect citizens. One way to reduce tax non-compliance is through compliance strategies which can be categorised into two; deterrence and accommodative approach. It is advisable that tax authority should not only focus on the deterrent approach (tax audit and penalty), mainly on tax offenders. Instead, tax authority also needs to find ways to preserve good taxpayers’ continuous fulfilment of their tax responsibilities, encourage future taxpayers to commit to tax laws, and transform tax offenders to become good taxpayers using the accommodative approach. This study uses the survey method to determine individual taxpayers’ perception of tax authority’s compliance strategies (threat of punishment, tax education programme, treatment provided by tax authority, special voluntary disclosure programme (SVDP)). This study then investigates the influence of those compliance strategies towards tax compliance behaviour. Our findings indicate that individual taxpayers have a positive perception towards compliance strategies provided by the tax authority in Malaysia (refer to Inland Revenue Board of Malaysia (IRBM)). In addition, the threat of punishment, treatment provided by IRBM and SVDP are significantly proven to have a positive relationship with tax compliance. However, it is suggested that IRBM should improve their tax education programmes as it is found to be insignificant. This study contributes to current tax compliance literature in a relatively important field of compliance strategies by providing comprehensive insights into the influence of both deterrence and accommodative apporaches in influencing tax compliance behaviour, as well as focusing more on an accommodative approach that is receiving attention lately. With both approaches in one study, the results of this study provide a clear, complete and comprehensive understanding since most of previous studies conducted separately. Finally, the findings of this study also provide valuable and significant input to the tax authorities and policymakers, especially IRBM in assessing and making a necessary improvement on their compliance strategies with the mission to enhance tax compliance behaviour, especially among individual taxpayers.